CACCT: An Automated Tool of Detecting Complicated Cardiac Malformations in Mouse Models. Issue 8 (20th February 2020) - Chu, Qing; Jiang, Haobin; Zhang, Libo; Zhu, Dekun; Yin, Qianqian; Zhang, Hao; Zhou, Bin; Zhou, Wenzhang; Yue, Zhang; Lian, Hong; Liu, Lihui; Nie, Yu; et al.
Abstract: Congenital heart disease (CHD) is the major cause of morbidity/mortality in infancy and childhood. Using a mouse model to uncover the mechanism of CHD is essential to understand its pathogenesis. However, conventional 2D phenotyping methods cannot comprehensively exhibit and accurately distinguish various 3D cardiac malformations for the complicated structure of heart cavity. Here, a new automated tool based on microcomputed tomography (micro‐CT) image data sets known as computer‐assisted cardiac cavity tracking (CACCT) is presented, which can detect the connections between cardiac cavities and identify complicated cardiac malformations in mouse hearts automatically. With CACCT, researchers, even those without expert training or diagnostic experience of CHD, can identify complicated cardiac malformations in mice conveniently and precisely, including transposition of the great arteries, double‐outlet right ventricle and atypical ventricular septal defect, whose accuracy is equivalent to senior fetal cardiologists. CACCT provides an effective approach to accurately identify heterogeneous cardiac malformations, which will facilitate the mechanistic studies into CHD and heart development. Abstract : An automated tool based on microcomputed tomography (CT) images known as computer‐assisted cardiac cavity tracking (CACCT) is established to identify complicated cardiac malformations in mice. With CACCT, researchers, even those without expert training or diagnostic experience of congenital heart diseases, can identify complicated cardiac malformations effectively, including transposition of the great arteries, double‐outlet right ventricle and atypical ventricular septal defect, whose accuracy is equivalent to senior fetal cardiologists.